2014
DOI: 10.1007/s10549-014-3069-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 is associated with epithelial-mesenchymal transition, breast cancer stem cell phenotype, and tumor progression in breast cancer

Abstract: MicroRNAs (miRNAs) are involved in the progression of breast cancer. Some miRNAs, especially the miR-200 family, miR-9, and miR-155 have been reported to be associated with epithelial-mesenchymal transition (EMT) and breast cancer stem cell (BCSC) phenotypes. This study was designed to evaluate the expression levels of these miRNAs in human breast cancer samples and analyzed their relationship with clinicopathologic features of the tumor including breast cancer subtype, EMT, BCSC phenotype, and prognosis. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 34 publications
5
97
0
1
Order By: Relevance
“…miR-9 has a well-recognized prometastatic function in human breast cancer (10,23), and it has been more recently associated with poor prognosis, EMT, and stemness features (11). Consistently, we found that higher miR-9 expression identified breast cancer patients with poor prognosis and associated with high histologic grade.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…miR-9 has a well-recognized prometastatic function in human breast cancer (10,23), and it has been more recently associated with poor prognosis, EMT, and stemness features (11). Consistently, we found that higher miR-9 expression identified breast cancer patients with poor prognosis and associated with high histologic grade.…”
Section: Discussionsupporting
confidence: 84%
“…Together with the internalization and degradation of PDGFRb upon stimulation, this provides a mechanism by which signaling through this receptor may be temporally limited. High levels of miR-9 have been associated with prometastatic function in human breast cancer (10), as well as with the acquisition of a mesenchymal and aggressive phenotype (11). On the other hand, members of the miR-200 family (five miRNAs organized in two clusters: miR200a/b/429 and miR-200c/141) are well-known negative regulators of EMT due to their direct targeting of several transcriptional factors implicated in the transition, such as ZEB1/2 and Snail (12).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of miR-9-mediated E-cadherin expression results in the activation of β-catenin signaling, which contributes to the upregulation of VEGF; in turn, this leads to increased tumor angiogenesis (80). Overexpression of miR-9 is also found in tumors with aggressive phenotypes, and is related to poor prognosis in breast cancer, suggesting that it may serve as a potential biomarker for the progression of breast cancer as well as a target for treatment (81).…”
Section: Emt-related Mirnas In Breast Cancermentioning
confidence: 99%
“…Patients with basal-like breast cancers frequently have poor prognosis, and are difficult to treat owing to the frequent lack of hormone receptors (a triple-negative phenotype with loss of ER and PR, and no HER2 amplification) that can be therapeutically targeted [138][139][140]. Six of these 16 basal-related miRNAs have been reported to be associated with basal-like/triple-negative breast cancer, including miR-9, miR-18 a, miR-19 a, miR-93, miR-106 b and miR-126 [141][142][143][144][145][146]. Noticeably, three miRNAs (miR-126, miR-143, miR-210) implicated in the DCIS-to-IDC transition are specifically dysregulated in basal-like IDC, suggesting that their deregulation plays a critical role in driving the progression of DCIS lesions to malignant basal-like IDC tumors (Table 2) Among luminal subtypes, luminal-B is a more aggressive subtype than luminal-A owing to low/negative expression of PR and/or HER2 overexpression, and high proliferation indicated by high Ki-67 [148].…”
Section: The Roles Of Mirnas In Breast Cancer Molecular Subtypesmentioning
confidence: 99%